'Biting the hand that feeds': fever and altered sensorium following a dog bite. Issue 12 (18th November 2011) - Hawkins, Joseph; Wilson, Ann; McWilliams, Eric
Abstract : Capnocytophaga canimorsus infection is the most severe and rapidly progressive bacterial infection transmitted by dog bite and fortunately is very rare. The authors describe a 68-year-old gentleman who presented in an acute confusional state 2 days after having been bitten on the left hand by a dog. Despite immediate broad-spectrum intravenous antibiotics, he developed significant sequelae including disseminated intravascular coagulopathy, microvascular emboli leading to peripheral necrosis, widespread local tissue destruction and septic arthritis. Our case illustrates a life-threatening presentation of infection with C canimorsus, which is known as 'the dog bite organism'. Early diagnosis and aggressive treatment is key to survival.